Correlation between volatile profiles and microbial communities: A metabonomic approach to study Jiang-flavor liquor Daqu. (July 2019) - Jin, Yao; Li, Dengyong; Ai, Mei; Tang, Qiuxiang; Huang, Jun; Ding, Xiaofei; Wu, Chongde; Zhou, Rongqing
Abstract: Microbial community diversity and volatile profiles of 14 Jiang-flavor liquor Daqu (JFLQ) samples were investigated by Illumina MiSeq platform and Head Space-solid Phase Microextraction Gas Chromatograph Mass Spectrometer (HS-SPME-GC-MS). Correlations between microbial community and volatile profiles of JFLQ were disclosed by redundancy analysis. Results indicated the outstanding high content of nitrogenous and aromatics compounds in Moutai Daqu samples, whereas esters were dominant for the samples from the brewing sites rather than Moutai. Bacillales, Enterobacteriales, and Lactobacillales were the dominant bacteria, while Candida, Trichoderma, Aspergillus, Trichosporon and Thermomyces were predominant in the fungal community. Compared to the randomly dispersed feature of fungi communities, bacterial communities had preferred "shelter": Lactobacillales mainly clustered in the surface of Daqu, whereas Bacillales in the core. Microbial interaction of JFLQ was stronger in the core than in the surface. Bacillales and Lactobacillales were closely positive-related with pyrazines and esters respectively, and Aspergillus was correlated with pyrazines, esters and aromatics. Based on the results, a metabolic map of abundant microorganisms in JFLQ was built up. Graphical abstract: Unlabelled Image Highlights: Volatiles were correlated with relevant microbial communities for Chinese JFLQ. Spatial characteristics of microbial colonies of JFLQ were revealed. Interactions of microbial colonies in JFLQ were explored. A summarized metabolic map of dominant microbes in JFLQ was built up.